A change of mood: The development of the Greek mood system - Philippaki-Warburton, Irene; Vassilios Spyropoulos (Linguistics, 2004)
This paper traces the steps in the changes of the Greek mood system, from the morphological one of Classical Greek, where mood was fused with tense and agreement within INFL, to the more syntactic one of Modern Greek, where mood occupies its own projection of MOODP. We show how the catastrophic loss of the morphological marking of the mood distinctions in the verb ending during the transition from Classical Greek to Hellenistic Koine was followed by (i) the emergence of a separate projection of a functional category MOOD inside the Comp-layer hosting the subjunctive/ indicative mood features followed by (ii) the grammaticalization of the conjunction hina to the subjunctive mood particle na and its transference from the C head to the separate MOOD head located between the C and the INFL heads and (iii) the subsequent relocation of the imperative from the INFL head to the MOOD head. We show that our analysis is consistent with the theories claiming that syntactic change is associated with formal features and the fixing of parameters.